The Preservation of The Traditional Performing Arts’ Sacred Place - Bhernadetta Pravita Wahyuningtyas (Humaniora, 2014)
This study explains the management of “Bharata” reputation, an Icon of classic, legendary, theatrical; traditional performing arts of Indonesia. Puppet has noble values in terms of moral education and philosophy of life; and “Bharata” becomes the "sacred" place for the preservation of the noble values of the puppet. “Bharata” is an institution that manages sustainable reputation and have to defend against the onslaught of competition from other institutions as a tourism destination. “Bharata” is a picture of a long journey and process of proving the majesty of traditional culture that owned by Indonesia. This study used post positivist paradigm. The nature of the study was descriptive and the selected approach was qualitative with in-depth interviews and observation for collecting data. Narrative analysis was used to analyze this study. The aim of this study has reviewed the reputation management of “Bharata” in its struggle of facing the globalization. The reputation management of “Bharata” is the results of coordination and socialization process within the institution; it is achieved through cooperation of each department by communication power.